Pedagogic practices in higher education in non-formal spaces in Manaus-AM - Lobo, Huanderson Barroso (2023)
This research aims to demonstrate the possibilities and why of working pedagogical practices in Higher Education in non-formal spaces in the city of Manaus - AM. This is research with a qualitative approach that presents the MUSA – Museu da Amazônia, located in the Jardim Botânico de Manaus Adolpho Ducke as a non-formal space. The research subjects were (07) postgraduate professors of the Higher Education Teaching course - DES, from a college in Manaus. For data collection, semi-structured questionnaires were used through a form applied in Google Forms. The research was carried out in three stages, as follows: (1) practical class; (2) application of questionnaires to teachers; (3) analysis and interpretation of the data obtained. The steps for data collection followed a chronological order, as Bardin (2016) organizes the content analysis: 1) pre-analysis; 2) exploration of the material and 3) treatment of results, inference and interpretation.